PERUBAHAN LINGKUNGAN, TRANSFORMASI ORGANISASIONAL DAN REPOSISI PERAN FUNGSI SUMBERDAYA MANUSIA - Gugup Kismono (UGM, 1999)
The environment within which an organization operates is dynamic and has become much more diverse nad complex. The environment has a profound impact on the organization's success. In today's changing, the firm faces many challenges not faced before. The company's ability to adopt or amend strategies to compensate for or take advantage of such changes will dictate its success and even survival.